Optimal allocation of intelligent parking lots in distribution system: A robust two‐stage optimization model - Motahareh Mojarad; Mostafa Sedighizadeh; Mohamad Dosaranian‐Moghadam (IET Electrical Systems in Transportation)
Abstract Electrification of transportation is one of the new ways to deal with environmental issues. In order to reach sustainable development, efficient integration of the plug‐in electric vehicles (PEVs) into the distribution network (DN) plays a significant role. Establishing PEV intelligent parking lots (IPLs) is one of the important solutions to develop charging stations. However, one of the problems with IPLs is restrictions created by municipalities and DNs while the common parking lots are not faced with these constraints. The aim of this paper is to optimally allocate IPLs in order to minimize system costs through a two‐stage mathematical model. The system cost involves installation cost, cost of exchanging the electrical power with an upstream grid, cost of the electrical power loss, network reliability cost, and emissions cost. In the first stage, the behaviour of IPLs is optimized taking into account the market interactions for enhancing the profit of the IPL owner. In the second stage, the optimal IPL allocation is performed taking various network constraints into consideration. The robust optimization is developed to hedge the DN operator and the IPL owner against risk imposed uncertain variables. The proposed model is a Robust Mix Integer Linear Problem, which is solved using the CPLEX solver in GAMS software. The effectiveness and the efficiency of the proposed model are evaluated on the IEEE 12‐bus test network.